2009
DOI: 10.1111/j.1440-0960.2009.00516.x
|View full text |Cite
|
Sign up to set email alerts
|

Electronic e‐isotretinoin prescription chart: Improving physicians' adherence to isotretinoin prescription guidelines

Abstract: Oral isotretinoin is a highly effective treatment for refractory nodulocystic acne. However, it can be associated with serious adverse effects such as teratogenicity and hepatitis. Inadequate cumulative dosing may also result in reduced therapeutic efficacy and higher disease relapse. A preliminary audit had previously revealed a poor and inconsistent adherence to local isotretinoin prescribing guidelines by physicians. To achieve greater than 90% adherence to isotretinoin guidelines for all acne patients pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…In contrast, Rademaker reported two pregnancies in his study (10) and 16 pregnancies were reported in a British Association of Dermatologists prospective audit of 75% of UK dermatologists in 2004 over a 6-month period (8). We believe that this is the result of close adherence to a strict protocol for isotretinoin prescription in our centre (15) as well as cultural perception or attitudes towards sexual behaviour.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…In contrast, Rademaker reported two pregnancies in his study (10) and 16 pregnancies were reported in a British Association of Dermatologists prospective audit of 75% of UK dermatologists in 2004 over a 6-month period (8). We believe that this is the result of close adherence to a strict protocol for isotretinoin prescription in our centre (15) as well as cultural perception or attitudes towards sexual behaviour.…”
Section: Discussionmentioning
confidence: 75%
“…Based on our institution's guidelines, these patients had a target cumulative dose of 120 mg/kg and were followed-up every 6-8 weeks whilst on isotretinoin therapy (15). Fasting serum levels of triglyceride, LDL, ALT and AST were measured at baseline and then repeated at the second visit.…”
Section: Data Collectionmentioning
confidence: 99%
“…18 In order to create safe and efficient guidelines, the electronic prescription system for isotretinoin (e-isotretinoin chart) was implemented in January 2005 at the National Centre of Singapore. 19 A comparison of doctors' compliance levels pre-and post-implementation was performed in key safety areas, such as obtaining consent, pregnancy testing, and other relevant laboratory investigations. This study was unique in its analysis from the physician's perspective and covered most (if not all) elements of safety concerns, including teratogenicity, and was mainly designed to assess implementation of the electronic isotretinoin prescription system in Singapore.…”
Section: Discussionmentioning
confidence: 99%
“…It was thus shown that the introduction of such electronic prescription systems has resulted in markedly improved physician compliance to isotretinoin treatment guidelines. 19 Provision of contraception is easy in Saudi Arabia, and one can access contraceptive devices without any problem. Indeed, hormonal contraceptive pills and intrauterine contraceptive devices are widely available across the country, and the overwhelming majority of Islamic scholars support modern non-permanent contraceptive use.…”
Section: Discussionmentioning
confidence: 99%
“…A well‐executed EMR system also offers patients seamless quality care 3,4 . NSC has previously embarked on a successful project tapping on EMR technology to ensure adherence to isotretinion prescription guidelines 5 …”
Section: Discussionmentioning
confidence: 99%